"What do coaches do" and "how do they relate": Their effects on athletes` psychological needs and functioning - Felton, L.; Jowett, S. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The sport psychology literature (e.g., Amorose & Anderson-Butcher, 2007; Bartholomew et al., 2011) has expressed the importance of coach behaviours, both supportive and controlling in various degrees, on athlete need satisfaction and ultimately well-being, however the importance of coach-athlete relationship quality on need satisfaction has hardly ever been explored. Grounded in self-determination theory, this study aimed to examine the links of the social environment, as defined by coach interpersonal behaviours and coach-athlete relationships, with athletes` perceptions of basic psychological needs and indexes of well-being. Methods: Athletes (N = 300) completed a multi-section questionnaire assessing the study variables. Structural equation modelling was used to produce a path model with EQS 6.1 (Bentler, 2002) in order to analyse the hypothesised associations between the study variables. In order to determine the adequacy of the model fit to the data various goodness-of-fit indexes were used including; the Satorra-Bentler scaled x² (S-Bx²), Robust Comparative Fit Index (CFI), Non-Normed Fit Index (NNFI), and the Root Mean Square Error of Approximation (RMSEA). Results: Structural equation modelling supported a model whereby coach behaviour of autonomy support and the quality of the coach-athlete relationship positively predicted athletes` satisfaction of needs, and in turn, satisfaction of needs predicted vitality, negative affect, and physical self-concept (self-descriptions of skilfulness and competence). Discussion: The findings suggest that, athletes` perceptions of supportive coaching behaviours and positive coaching relationships may serve to fulfil important psychological needs. Subsequently, these manifested connections may promote athletes` well-being while thwarting their ill-being. These findings support theoretical assumptions and highlight that athletes` perceptions of what coaches do, and how they relate, are important to their psychological needs satisfaction and optimal functioning.